Ta'tsir al-wasilah as-sam'iyyah al-bashariyyah fi ta'allum maharah al-istima' li al-lughah al-'arabiyyah 'ala mukhtalif al-mustawayat. - Farhan, Ali; Sopian, Asep (Universitas Negeri Malang, 2024)
This study aims to identify the general trends in the impact of audio-visual media. The research examines the effects of audio-visual media on listening skills and motivation in Arabic language learning, considering educational levels, research design, and the types of audio-visual media used. The results indicate that at the primary school level, animation media such as Animaker and cartoons are highly effective in enhancing listening skills and student motivation, as they offer an interactive and enjoyable learning experience. At the junior high school level, the use of interactive videos and popular platforms like YouTube shows significant improvements in listening skills and fosters student engagement through media that is familiar to their daily lives. At the senior high school level, the integration of complex content such as films and YouTube videos enhances listening skills and motivates students by connecting language learning to real-world contexts. Meanwhile, in higher education, more authentic audio-visual media, such as subtitled videos and films, help develop deeper listening skills, expand vocabulary, and encourage self-reflection through exposure to culturally rich content. Motivation for learning also progresses steadily, starting from an interest in animation at the primary level to an appreciation for contextual content at the higher education level. Overall, the study highlights the importance of adapting the type of audio-visual media according to the developmental stages of learners, thus supporting optimal listening skills and learning motivation at each educational level. The findings underscore the need for a targeted approach in media selection, considering the alignment between media and students' real-world interactions.